Utilization of agrowaste including cocoa, pineapple, sugar canes and other crops for the production of ethanol - Abdul Samah, Othman; Mohd. Nor, Othman; Alimon, Hasimah (1989)
With the increasing demand for energy, the production of ethanol from a cheap fermentable sugar source assumes greater importance especially in non-producing oil countries. For an agriculturql country which has an abundance of agrowaste resources,ethanol could be an alternative source of biofuel. About 107. ethanol could be produced from cocoa waste and approximately 77. from pineapple waste by continuous fermentation using S. cerevisiae (wild strain). -In batch culture, immobi1ized cells of S. cerevisiae were capable of producing 36 g 1-1 of ethanol in cocoa waste and 49 g 1-1 in sugar cane respectively, after about 15-20 hours of incubation. Substantial amounts of ethanol were also obtained from local fruits such as Achras sabota and Musa sp.